Mechanical behaviour of nanocomposites - Lai, Yongshen (2011)
Although the mechanical properties of carbon nanotubes (CNTs) have been studied extensively, the long term behaviour of CNTs or composites reinforced by this material is often left out. In this project, the creep behaviour of single-walled carbon nanotubes (SWNTs) embedded in PVB matrix was investigated. SWNT/PVB composite fibers underwent tensile tests to determine their ultimate stress then creep tests to find out how they react under constant loading for a long period of time. The experimental results show that a fatigue limit begins to appear when 65% of the ultimate stress is applied as SWNT/PVB fibers remain intact after one day of stretching at this load level.